Resistensi Penghuni Rumah Susun Pada Revitalisasi Rusun di Kecamatan Bukit Kecil Kota Palembang - Asmaran Dani; Yunindyawati; Ridha Taqwa (Jurnal Sosiologi Nusantara, 2025)
The resistance of flat residents in Bukit Kecil District, Palembang, is a response to the government's revitalisation policy aimed at overcoming urban slum conditions and promoting modern housing. Although the city government intends to beautify the area and eliminate negative perceptions, residents reject the plan due to structural problems. This study aims to explore the root causes of apartment residents' resistance to the revitalisation policy. Using qualitative methods and Hollander and Einwohner's resistance theory approach, data were collected through in-depth interviews, observations, and documentation. The use of narratives enables researchers to understand apartment residents' perspectives through their life experiences. A total of 9 informants, including residents, community leaders, and provocateurs, were interviewed to uncover the background of resistance, both individually and collectively. This study emphasises action and opposition as dimensions of resistance analysis. The research findings reveal that resistance stems from unclear administration and the existence of criminal business. Residents often lack legal proof of ownership, despite having long occupied the house. In addition, illegal activities such as drug distribution and prostitution are economically rooted in the lives of apartment residents. The study concludes that resistance is not only emotional but also a complex expression of legal ambiguity, economic survival, and distrust of authority.